2011
DOI: 10.1089/jwh.2010.2057
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Gender Equity in Health Using Gender-Sensitive Indicators: A Cross-National Study

Abstract: This study shows that gender inequities in health exist in all countries, regardless of income level. Economic development seemed to confer advantages in the availability of such indicators; however, this finding was not consistent and needs to be further explored. Future initiatives should include identifying health system factors and risk factors associated with disparities as well as assessing the cost-effectiveness of including the routine monitoring of gender inequities in health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
0
11
1
1
Order By: Relevance
“…The research community often fails to recognize the interaction between gender, social factors and health outcomes. Despite the clear need for such information to shape programs, sex-disaggregated data is still not systematically collected [6,9].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The research community often fails to recognize the interaction between gender, social factors and health outcomes. Despite the clear need for such information to shape programs, sex-disaggregated data is still not systematically collected [6,9].…”
Section: Methodsmentioning
confidence: 99%
“…Evaluating the health impact of these gender inequities is undermined by the lack of consensus regarding the most relevant indicators and how best to interpret these measures. Some authors have suggested a comprehensive mix of indicators including health status (maternal mortality as well as rates of sexual violence), health system data (insurance coverage, catastrophic expenditures, consultations), literacy and education, socio-economic status and employment, and political empowerment [9,19]. However, health information systems and other mechanisms to gather routine data are disrupted in conflictaffected environments and sex-disaggregated information is scarce.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These relative disadvantages for women in terms of wages and employment are closely linked to high levels of mortality during and after childbirth (Shen & Williamson, 1999;United Nations [UN], 1990). Addressing gender-sensitive indicators is vital for assessing the poor health outcomes of mothers (Diaz-Granados et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[1] Not only are women more likely to have higher rates of blindness, but they are also less likely to access appropriate eye services. Several studies have documented such disparities.…”
mentioning
confidence: 99%